What Drives Political Engagement of the Young Generation? A Political Psychology Study - Muhammad Zulfa Alfaruqy; Anandaru Padmonurcahyo (Indonesian Center for Religion and Society Studies (InTReSt), 2023)
Political engagement of the young generation is needed for a democratic country, including Indonesia. However, political engagement has psychological challenges for the younger generation. This study aimed to determine the political engagement level of the young generation and some factors that influence it. The research was designed with mixed methods. The political engagement scale (16 items; α =0.862) was administered with an open-ended questionnaire to 600 students. Interviews to deepen the answers to the questionnaire were conducted with 6 participants (3 male, and 3 female). The results indicate that the political engagement of the young generation, especially college students, is in the high category. Factors that influence political engagement include personal factors (motivation to contribute and personal interest), national condition factors (perception of the nation's condition and perceived influence), information access factors, and social-environmental factors. This finding complements previous research, that personal factors are the most powerful in influencing student political involvement. The research has implications for government institutions, education, political parties, and families in influencing the political engagement of the younger generation with effective strategies.